Ethnobotanical study of wild edible plants in Arsi Robe district of East Arsi Zone, Ethiopia - Sisay Biri; Bereket Ayenew; Getu Dida; Ayalew Sebsibe; Fekadu Gurmessa; Bizuneh Woldeab; Gashaw Awlachew; Zewdie Kassa; Moa Megersa (BMC, 2024)
Abstract Background Wild edible plants (WEPs) are usually considered to constitute all plant resources that are neither cultivated nor domesticated but are used as nutritional supplements by local people. WEPs play a vital role in ensuring food and livelihood security for countless families and communities around the world. The objective of the study was to assess and document wild edible plants used by communities in the Arsi Robe district as food. Methods Semi-structured interviews, market surveys, and guided field walks were employed as data collection tools. The data were analyzed using preference ranking, direct matrix ranking, and Jaccard's similarity index. Results The present study revealed various types of wild edible plants consumed by local communities in the Arsi Robe district of the East Arsi Zone. This could be justified by the documentation of 36 different wild edible plants in the study area. These WEPs belong to 31 genera and 25 families. Most of the growth forms of the edible wild plants in the district were shrubs (16, 44.44%) and trees (14, 38.88%). Amaranthus caudatus and Bridelia micrantha are the most preferred WEPs in the study area. The finding of the study also revealed that Lepidotrichilia volkensii and Premna schimperi are among the novel WEPs that had not before been documented as food items in other areas. Olea europaea subsp. cuspidata, Ficus sycomorus, Cordia africana, and Ficus sur are species with multiple uses. Agricultural expansion, charcoal production, the construction of different materials, making agricultural tools, deforestation, and other factors were the top prioritized threats affecting the abundance and diversity of wild edible plants. Conclusion Along with the sustainable utilization and conservation of the existing WEPs of the study district, priority should be given to the urgent collection, domestication, and cultivation of multiuse wild edible plant species such as Olea europaea subsp. cuspidata, Ficus sycomorus, Cordia africana, and Ficus sur in the study area.